Pooled Prevalence and Determinants of Completion of Maternity Continuum of Care in Sub-Saharan Africa: A Multi-Country Analysis of Recent Demographic and Health Surveys - Melaku Hunie Asratie; Daniel Gashaneh Belay; Daniel Gashaneh Belay (Frontiers Media S.A., 2022)
BackgroundImproving the coverage of completion of the maternity continuum of care is the priority area of sub-Saharan African countries to achieve the sustainable development goal. Despite this, information is scant about the pooled prevalence of completion of the maternity continuum of care and its determinants in sub-Saharan African countries. Therefore, this study aimed to assess the pooled prevalence of completion of the maternity continuum of care and its determinants among women in sub-Saharan African countries.MethodsThe study was conducted based on Demographic and Health Survey (DHS) data from 33 sub-Saharan African countries from 2010 to 2020. The total sample size of 337,297 postpartum period women with children aged 0-36 months (about 3 years) was employed in the analysis by STATA version 14. A multilevel logistic regression model was fitted, and intraclass correlation coefficient (ICC), median odds ratio (MOR), proportion change in variance (PCV), and deviance were used for model fitness and comparison. Adjusted odds ratio (AOR) with its 95% confidence interval (CI) was presented. Variables with a value of p < 0.05 were declared significant determinants of completion of the maternity continuum of care.ResultsThe pooled prevalence of completion of the maternity continuum of care was 35.81%; [95% CI, 35.64%, 35.9%]. Higher educational level [AOR = 3.62; 95% CI 2.25, 4.46], wanted pregnancy [AOR = 2.51; 95% CI 1.82, 3.12], history of terminated pregnancy [AOR = 3.21; 95% CI 2.86, 4.21], distance to the nearby health facility [AOR = 2.11; 95% CI 1.68, 2.36], women as primary decision maker [AOR = 2.15; 95% CI 2.02, 2.87], nouse of traditional medication during pregnancy [AOR = 1.01; 95% CI 1.00, 1.45], antenatal care (ANC) visit within second trimester [AOR = 2.76; 95% CI 2.01, 3.47], informed about pregnancy complication [AOR = 2.73; 95% CI 2.10, 3.21], healthcare provider support [AOR = 1.77; 95% CI 1.02, 2.44], and being eastern and western African [AOR = 1.55; 95% CI 1.11, 2.44 and AOR = 2.01; 95% CI 1.88, 2.76, respectively] were determinant factors of completion of maternity continuum of care.ConclusionsThe completion of the maternity continuum of care in sub-Sahara African countries was low. Emphasis on women's education, type, history of pregnancy, distance to the nearby health facility, region, assessing the exposure of traditional medication, and informed about pregnancy complications, healthcare provider's support can improve the prevalence of completion of the maternity continuum of care.